Comparison Between Eight- and Sixteen-Channel TEM Transceive Arrays for Body Imaging at 7 Tesla - Snyder, CJ (2011)
Eight- and sixteen-channel transceive stripline/TEM body arrays were compared at 7 tesla (297 MHz) both in simulation and experimentally. Despite previous demonstrations of similar arrays for use in body applications, a quantitative comparison of the two configurations has not been undertaken to date. Results were obtained on a male pelvis for assessing transmit, SNR and parallel imaging performance and to evaluate local power deposition versus transmit B(1) (B(1)(+)). All measurements and simulations were conducted after performing local B(1)(+) phase shimming in the region of the prostate. Despite the additional challenges of decoupling immediately adjacent coils, the sixteen-channel array demonstrated improved or nearly equivalent performance to the eight-channel array based on the evaluation criteria. Experimentally, transmit performance and SNR were 22% higher for the sixteen-channel array while significantly increased reduction factors were achievable in the left-right direction for parallel imaging. Finite-difference time-domain simulations demonstrated similar results with respect to transmit and parallel imaging performance, however a higher transmit efficiency advantage of 33% was predicted. Simulations at both 3T and 7T verified the expected parallel imaging improvements with increasing field strength and showed that, for a specific B(1)(+) shimming strategy employed, the sixteen-channel array exhibited lower local and global SAR for a given B(1)(+).